Sexual and Gender-Based Violence in the Kivu Provinces of the Democratic Republic of Congo : Insights from Former Combatants - Elbert, Thomas; Hinkel, Harald; Maedl, Anna; Hermenau, Katharin; Hecker, Tobias; Schauer, Maggie; Riedke, Heike; Winkler, Nina; Lancaster, Philip (World Bank, Washington, DC, 2014)
Ending the period of conflict, violence and insecurity in Eastern DRC would contribute tremendously to addressing the high levels of ongoing Sexual and Gender-Based Violence (SGBV). This study has been conducted in partnership with the Non-Governmental Organization (NGO) vivo international, to determine individual motivations, as well as strategic or tactical aspects of sexual violence of different armed groups and their leadership. SGBV is a complex problem requiring an integrated and multi-sectoral response, even more so in a fragile environment with ongoing conflict, such as in Eastern DRC. Responses to violence against women need to address, among others: health sector including physical and mental health issues, the criminal-justice sector, economic empowerment, community development (promoting equitable access to resources for women and men), prevention of violence (e.g., through formal and informal education), and advocacy at the community, national and international levels. Any effective response must combine enforcing laws and prosecuting perpetrators to break the cycle of impunity, while addressing the individual and societal wounds, and working to prevent a normalization and recurrence of sexual violence.